Elastic Modulus of Foamcrete in Compression and Bending at Elevated Temperatures - Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2012)
This paper will presents the experimental results that have been performed to examine and characterize the mechanical properties of foamcrete at elevated temperatures. Foamcrete of 650 and 1000 kg/m3 density were cast and tested under compression and bending. The tests were done at room temperature, 100, 200, 300, 400, 500, and 600°C. The results of this study consistently demonstrated that the loss in stiffness for cement based material like foamcrete at elevated temperatures occurs predominantly after about 95°C, regardless of density. This indicates that the primary mechanism causing stiffness degradation is microcracking, which occurs as water expands and evaporates from the porous body. As expected, reducing the density of LFC reduces its strength and stiffness. However, for LFC of different densities, the normalised strength-temperature and stiffnesstemperature relationships are very similar.